Mindful Play Counseling in Early Childhood Education: Evidence from a Systematic Review of Interventions for Ages 4-6 - Dinar Mahdalena Leksana; Mochamad Nursalim; Elisabeth Christiana; Endang Pudjiastuti Sartinah; Titin Indah Pratiwi (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This article aims to summarize the empirical evidence on the effects of mindful play interventions on self-regulation, executive function, social competence, and conflict resolution in children aged 4–6 years, and to assess their relevance to the development of Early Childhood Guidance and Counseling (BK PAUD) services. Using the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines, 36 articles from Scopus, ScienceDirect, and Google Scholar were analyzed through thematic synthesis. The results showed that mindful play consistently improved emotion management skills, impulse control, cognitive flexibility, empathy, and conflict resolution strategies. Teacher and parent support play a significant role in strengthening the effectiveness of interventions. These findings provide a conceptual and empirical basis for developing Mindful Play Counseling as an evidence-based BK PAUD service model. Theoretical, practical, and policy implications are discussed to strengthen the implementation of mindful play in early childhood education. Keywords: conflict resolution, early childhood education, executive functions, mindful play, self-regulation